Emergency Medicine Simulation Scenario: First-Trimester "Septic" Abortion - Jonathan Davis; Lauren Weinberger (Association of American Medical Colleges, 2011)
Abstract This case scenario is used to demonstrate effective communication skills with an underage patient and her parents when evaluating a pregnancy-related complication, identify a gynecologic etiology of undifferentiated low abdominal pain in a reproductive-age female patient, and effectively and appropriately manage a first-trimester pregnancy complication (septic abortion). The case scenario is suitable for simulation training in a wide range of acute care medical specialties, as well as preparation for the oral board examination in emergency medicine. The target audience is medical students, medical residents, or attending physicians in the emergency department setting. In addition, it can be utilized for other medical specialties, including obstetrics and gynecology, family medicine, and adolescent medicine. It is optimal to have a standardized patient for this scenario. If this is not feasible, a low-fidelity or high-fidelity manikin can be utilized as an alternative. Necessary additional roles include a treating physician being evaluated and one nurse, as well as the instructor who controls the scenario and acts as both the historian and any consulting physicians. Other participants may serve as additional staff to be directed by the treating physician and/or family. This case has been utilized as a mock oral board training case for emergency medicine residents and faculty members preparing for the oral board examination, which, along with a written examination, is required for board certification in emergency medicine. Approximately 30 learners have used this case over the course of several years. The case materials have been continuously refined and revised based on feedback from both faculty examiners and learners.